Effect of Traditional Chinese Medicine comprehensive nursing interventions on prevention of abdominal distension and constipation after unilateral total knee replacement (中医综合护理预防单侧全膝关节置换术后腹胀便秘的效果观察) - ZHANG Pan (张盼); KONG Hua (孔华); XING Liang (邢亮) (中西医结合护理)
Objective To investigate the effect of Traditional Chinese Medicine (TCM) comprehensive nursing interventions on prevention of abdominal distension and constipation after unilateral total knee replacement. Methods A total of 120 patients undergoing unilateral total knee arthroplasty were randomly divided into 2 groups. The control group (n=60) used conventional nursing measures to prevent postoperative abdominal distension and constipation. In the observation group(n=60), comprehensive nursing interventions including Chinese medicine hot election bag, constipation massage therapy combined with acupoint application were carried out. The incidence of postoperative constipation was s compared between the two groups, and the degree of postoperative abdominal distension was measured. Results There was no significant difference in the incidence of constipation at 24 hours after operation between the two groups (P＞0. 05). The incidence of constipation in the observation group was lower than that in the control group at 48 h, 72h and the 7 days after operation, with statistical significance (P＜0. 05). A lower degree of abdominal distension was reported in the observation group than that of the control group at 24 h, 48 h, 72 h and 7 days after surgery, with statistical significance(P＜0. 05). Conclusion The combined application of TCM comprehensive nursing interventions can effectively relieve abdominal distention and reduce the incidence of constipation in patients after unilateral total knee replacement, and promote early postoperative defecation. (目的 探讨中医综合护理干预预防单侧全膝关节置换术后腹胀和便秘的效果。方法 单侧全膝关节置换术患者120例随机分为对照组和观察组, 各60例。对照组采用常规方法预防术后腹胀和便秘, 观察组在常规护理基础上增加中医综合护理干预, 包括中药热奄包、便秘推拿治疗联合穴位贴敷。记录两组术后便秘发生情况, 评价两组术后腹胀程度。结果 两组患者术后24 h便秘发生率比较, 差异无统计学意义(P＞0. 05); 术后48 h、72 h及术后第7天, 便秘发生率观察组均低于对照组, 差异有统计学意义(P＜0. 05)。术后24 h、48 h、72 h及术后第7天腹胀程度评价结显示, 观察组较对照组轻微, 差异有统计学意义(P＜0. 05)。结论 中医综合护理能有效缓解单侧全膝关节置换手术患者术后腹胀程度, 降低术后便秘发生率, 促进患者术后早期排便。)